1991
DOI: 10.1111/j.1751-1097.1991.tb02003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biphotonic Photoionization of Chlorpromazine During Conventional Flash Photolysis: Spin Trapping Results With 5,5‐dimethyl‐1‐pyrroline‐n‐oxide

Abstract: A novel combination of conventional flash photolysis and electron spin resonance (ESR) spin-trapping has been used to demonstrate that photoionization of chlorpromazine (CPZ), and the concomitant production of hydrated electron, occurs through a stepwise biphotonic mechanism during conventional flash photolysis at wavelengths above 290 nm. The production of hydrated electron in the flash photolysis experiment has been monitored and quantified through the use of the spin trapping agent, 5,5-dimethyl-1-pyrroline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Deca-BDE absorbs readily in the wavelength range passed by a 309 nm filter, but there is no absorbance above ~350 nm (Figure S1). THF, DMF, toluene, and DMPO (λ max = 230 nm, ε 228 = 7.7 × 10 3 M −1 cm −1 ) (28) do not absorb significantly in this range (Figure S1). Thus, the activating wavelength for radical formation from deca-BDE is in the UVA (400-320 nm) to UVB (320-280 nm) range.…”
Section: Resultsmentioning
confidence: 99%
“…Deca-BDE absorbs readily in the wavelength range passed by a 309 nm filter, but there is no absorbance above ~350 nm (Figure S1). THF, DMF, toluene, and DMPO (λ max = 230 nm, ε 228 = 7.7 × 10 3 M −1 cm −1 ) (28) do not absorb significantly in this range (Figure S1). Thus, the activating wavelength for radical formation from deca-BDE is in the UVA (400-320 nm) to UVB (320-280 nm) range.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it decays by a first-order kinetics (likely because of the interaction with a molecule of drug in the ground state); its kinetics was not affected by the presence of molecular oxygen and was sensitized in acetonitrile by chloranil, a well-known electron acceptor in the triplet state (30)(31)(32)(33). This behavior is in agreement with that already reported for similar compounds (34). The spectral and kinetic properties of the transients detected in water are shown in Table 4, together with the absorption coefficients of the cation radicals and the photoionization quantum yields.…”
Section: Photophysical Resultsmentioning
confidence: 99%
“…As already reported for CPZ [30][31][32][33], laser flash experiments with these phenothiazines derivatives indicate the occurrence of monophotonic ionization of the substrate, even if a scarce contribution of a biphotonic pathway cannot be excluded, as suggested for CPZ by conventional flash photolysis [35] and the two-color, twopulse excitation method [36] described above.…”
Section: Photophysical Characteristics Of Phenothiazinesmentioning
confidence: 59%
“…Thus phenothiazines photoionization has been clearly demonstrated by several groups using transient absorption spectroscopy or EPR, but controversy remains over the mechanism of photoionization of these compounds. Motten et al [33], Buetner et al [34] and Hall et al [35] in contrast to the previous works proposed a wavelength-dependent photoionization of CPZ and promazine (PMZ) involving stepwise biphotonic photoionization through the triplet state at wavelength> 280 nm and monophotonic photoionization at wavelength <300 nm: this wavelength dependence suggest that the mechanism for cutaneous phototoxicity associated with clinical use of CPZ, which occur at solar wavelength >300 nm does not involve photoionization. More recently Garcia et al [36] in an elegant study using conditions where absorption by singlet or triplet excited states occur selectively have confirmed that photoionization occurs through biphotonic excitation for CPZ and PZ.…”
Section: Photophysical Characteristics Of Phenothiazinesmentioning
confidence: 90%